МОНИТОРИНГ ФИЗКУЛЬТУРНО-ОЗДОРОВИТЕЛЬНОЙ РАБОТЫ В СЕЛЬСКИХ ОБЩЕОБРАЗОВАТЕЛЬНЫХ ШКОЛАХ - Усмонов, З.Н. (SCIENCE and SOCIETY, 2020)
The article discusses the results of monitoring pedagogical research on conducting basic classes in physical culture and improving the physical education and health activities of the pedagogical team of subject teachers working in rural educational institutions.